(untitled) (Shaheed Smriti Journal, 2024)
This research study critically examines the emotional and psychological trauma experienced by the protagonist, Amir, in The Kite Runner by Khaled Hosseini. The novel provides a profound exploration of guilt, redemption, and the enduring psychological repercussions of past transgressions. Through an in-depth analysis of key themes, including guilt, forgiveness, and redemption, this research investigates the extent to which Amir’s psychological trauma shapes his behavior, interpersonal relationships, and self-perception. By engaging with relevant psychological theories and direct textual analysis, this study highlights the novel’s nuanced depiction of trauma, offering broader insights into the human experience of coping with remorse and the pursuit of emotional restoration. The findings underscore the centrality of guilt and trauma in Amir’s character arc, demonstrating their pivotal role in his ultimate path to redemption.